2016
DOI: 10.1021/acsami.6b07347
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Active Thin Carbon Films with Enhanced Adhesion to Silicon Substrates

Abstract: Thin carbon films deposited on technologically relevant substrates, such as silicon wafers, can be easily implemented in miniaturized electrochemical devices and used for sensing applications. However, a major issue in most carbon films is the weak film/substrate adhesion that shortens the working device lifetime. This paper describes the facile preparation of robust thin carbon films on silicon/silicon oxide substrates by one-pot sol-gel synthesis. The improved adherence of these carbon films is based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Details about the deposition of RF/SiO 2 films and the pyrolysis process to generate the corresponding C/SiO 2 films on Si substrates of different dimensions (from 2 × 2 cm 2 to 4 in. wafers) through spin‐coating RF/APTES sol solutions, can be found elsewhere . The key point of the process was the incorporation of APTES to RF sols that greatly enhanced the interfacial adhesion of the resulting sol–gel films to Si substrates containing a thermally grown SiO 2 surface layer, without significantly affecting the electrical properties of the resulting carbon thin‐films.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details about the deposition of RF/SiO 2 films and the pyrolysis process to generate the corresponding C/SiO 2 films on Si substrates of different dimensions (from 2 × 2 cm 2 to 4 in. wafers) through spin‐coating RF/APTES sol solutions, can be found elsewhere . The key point of the process was the incorporation of APTES to RF sols that greatly enhanced the interfacial adhesion of the resulting sol–gel films to Si substrates containing a thermally grown SiO 2 surface layer, without significantly affecting the electrical properties of the resulting carbon thin‐films.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, lithographic processes, including conventional photolithography and soft lithography, have been used to directly pattern sol–gel materials in the fabrication of lab‐on‐a‐chip devices. Recently, we have developed a one‐pot sol–gel approach for preparing carbon/silica (C/SiO 2 ) thin films that addresses the limitation of poor adhesion to silicon wafers . These C/SiO 2 films show a remarkably strong interfacial adhesion to Si/SiO 2 substrates thanks to the formation of siloxane chemical bonds (SiOSi) between the silanol groups on both the substrate and the material.…”
Section: Introductionmentioning
confidence: 99%
“…These films are based on the simultaneous gelation of the 3‐aminopropyltriethoxysilane (APTES) silica precursor and resorcinol/ formaldehyde carbon precursors, in a one‐pot synthesis process. We have also demonstrated that these films exhibit good homogeneity and excellent electrochemical performance . Moreover, different lithographic‐based microfabrication approaches were tested to pattern these films and thus produce carbon based thin film electrochemical sensors (Figure , route B) .…”
Section: Electroanalytical Devices Made With Resorcinol‐formaldehyde mentioning
confidence: 91%
“…Initially, carbon/silica (C/SiO 2 ) films were produced in order to study the film's electrical and mechanical properties. The preparation of these films has been previously reported by our group [22], and applied in this work with some variations. Details about the reagents and materials used in this synthesis can be found in the SI.…”
Section: Preparation Of C/sio 2 Filmsmentioning
confidence: 99%